2019
DOI: 10.1186/s12909-019-1614-y
|View full text |Cite
|
Sign up to set email alerts
|

Obesity education in the family medicine clerkship: a US and Canadian survey of clerkship directors’ beliefs, barriers, and curriculum content

Abstract: Background Despite concerns regarding the increasing obesity epidemic, little is known regarding obesity curricula in medical education. Medical school family medicine clerkships address common primary care topics during clinical training. However, studies have shown that many family physicians feel unprepared at addressing obesity. The purpose of this study was to evaluate factors related to obesity education provided during family medicine clerkships as well as identify future plans regarding ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…[37][38][39][40] Alternatively, this may reflect the lack of effective obesity management solutions available that could help patients attain their weight loss goals causing patients to turn to unproven therapies with large weight loss claims. Further, the low reported use of dietitians may indicate the lack of availability of dieticians or inadequate training for dieticians 41 and medical professionals 42,43 in Canada for treating obesity.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40] Alternatively, this may reflect the lack of effective obesity management solutions available that could help patients attain their weight loss goals causing patients to turn to unproven therapies with large weight loss claims. Further, the low reported use of dietitians may indicate the lack of availability of dieticians or inadequate training for dieticians 41 and medical professionals 42,43 in Canada for treating obesity.…”
Section: Resultsmentioning
confidence: 99%
“…The study concluded that there is still a potential need for clerkship directors and others involved in family medicine education to assess their own biases regarding obesity and better preparing the doctors of the future. [ 50 ] In our study, we aimed to increase undergraduate medical students' abilities to assess BMI, body composition monitor, and anthropometric measurements together with increasing their ability to sort the obese persons who have eating disorders that need interventions and behavioral therapy by using EAT score. Overall, the results of this study can provide essential data for designing educational programs to prevent abnormal eating attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…With medical education in particular, North American undergraduate medical schools incorporate little training in evidence-based obesity management [ 20 , 23 ]. For example, previous studies exploring obesity-related medical education in US and Canadian family medicine clerkship programs noted that obesity was most commonly taught in curricula in the context of obesity-related complications (e.g., diabetes), or during discussion on lifestyle behavioural changes such as modifications in diet and exercise [ 23 ]. Current research and the Canadian Obesity Adult Management Guidelines put an emphasis on the biological and genetic aspects of obesity, and on mitigating bias and discrimination in obesity medicine [ 1 ].…”
Section: Current Education On Obesity Management and Future Directionsmentioning
confidence: 99%